Dubbing television advertisements across cultures and languages: A case study of English and Arabic - Ahmad S. Haider; Faurah Alrousan (Universitat Jaume I. Department of English Studies, 2022)
The differences between Arab and English cultures make the task of Translating English advertisements into Arabic challenging. This study investigates the strategies used by translators to dub English advertisements into Arabic. Six English advertisements and their Arabic translation were compiled from YouTube and then compared their contents, Brand's name, and catchphrases. The findings showed that the translators opted for using various translation strategies such as cultural adaptation, substitution, loan, transliteration, explicitation, addition, omission, and paraphrasing. The analysis also revealed that translators sometimes use the literal translation approach to preserve the foreignness spirit and stay faithful to the original message. They also followed the free approach of translation to bridge the cultural gap. The study recommends future researchers to examine other advertisements in different domains.